Achieving Diversity and Inclusivity in Teaching and Learning : Final Report for 1997 Staff Development Grant. - Mann, Sarah; Black, Barbara (Committee for University Teaching and Staff Development (CUTSD), 1999)
This is the final project report for a 1997 Staff Development Grant funded by the Committee for University Teaching and Staff Development. The project aimed to heighten an awareness of diversity and inclusive teaching and learning issues in higher education through a range of activities including an ongoing series of workshops which aimed to assist teaching staff to: recognise that each student (and teacher) brings a unique culture to the classroom; enhance creative problem-solving by actively engaging the 'multiple perspectives' found in any classroom; build 'cultural bridges' to enable all students to participate fully; create environments where students are encouraged, and their personal identity honoured; and recognise the importance of being positive role models for co-responsibility. The report details the Inclusivity project and provides justification and an educational rationale for its development.